Assessing Organizational Readiness for Change; Comment on "Development and Content Validation of a Transcultural Instrument to Assess Organizational Readiness for Knowledge Translation in Healthcare Organizations: The OR4KT" - Lisa M. Puchalski Ritchie; Sharon E. Straus (Kerman University of Medical Sciences, 2019)
This commentary provides an overview of the organizational readiness for change (ORC) literature over the last decade, with respect to prevailing definitions, theories, and tools to guide assessment of ORC in preparation for implementation. The development of the OR4KT by Gagnon et al is an important contribution to this body of work. This commentary highlights the strengths of the OR4KT including development based on two systematic reviews conducted by the authors to synthesize OR theory and measurement tools, and applicability to a wider range of high-income country healthcare settings through inclusion of input from a diverse group of international experts and transcultural adaptation of the tool, in the context of the literature to date. Limitations and future directions for further development of the tool are also discussed and include application of quantitative psychometric approaches and evaluation of the tool in a broader range of healthcare settings.